The Politics of Belonging and Implications for School Organization: Autophotographic Perspectives on "Fitting In" at School - Jeff Walls; Karen Seashore Louis (SAGE Publishing, 2023)
The notion of belonging is an often-referenced but under-theorized concept in studies of school organization. The purpose of this study is to examine the politics of belonging in schools and accompanying implications for how schools are organized and led. This research employs an autophotographic methodology. Student participants took photographs across 2 years of data collection of spaces where they did and did not "fit in" and participated in interviews to explain their photographs. Students identified four themes in their photographs regarding their sense of membership at school: (a) the importance of spaces where belonging is noncontingent; (b) the distinction between calm spaces and surveilled spaces; (c) anxiety in public, "wild" spaces where no help was available; and (d) generally positive but mixed impressions of teachers. An increased understanding of organization leadership for belonging is linked to numerous other timely concerns in educational administration, including equity and inclusion.